Farmers’ Intention to Apply for National Health Insurance (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
The number of people who worked as farmers is big enough to challenge the Healthcare Social Security Agency (BPJS Kesehatan) to achieve these targets. This study aims to determine the variables associated by the intention of farmers to apply for National Health Insurance in the working area of Sungai Rambutan Integrated Independent City Community Health Center in Ogan Ilir Regency. The type of this research is descriptive analytical research with a cross-sectional design. The samples used farmers in the work area of Sungai Rambutan public health center. 104 samples were selected by cluster random sampling. 57.7 % of the farmers have the intention to apply for national health insurance. There are five variables related to the intention of farmers to apply for national health insurance. Those variables are the behavioral beliefs, the outcome evaluation, motivation to comply, control beliefs, and perceived power. The outcome evaluation was the most dominant variable associated with the intention to apply for national health insurance since it controlled the other variables. To increase the number of national health insurance members, approaching local stakeholders to introduce and educate all people to apply and inform the benefit of national health insurance is required